BETWEEN OPPRESSIONS, PRAXIS, AND RESISTANCES: INTERSECTIONALITY AND THE CENTRALITY OF BLACK WOMEN IN THE BRAZILIAN SOCIAL STRUCTURE - Ikuta, Ávila Smitiely de Abreu Lima; Pinheiro, Juliana da Luz Lima de Arruda; Ribeiro, Suellen Aparecida Viana; da Silva, Rosane Penha Mendes; Carreiro, Carolina Martins; Leonel, Rosilene Mirian Costa; Cebalho, Eva da Silva; Catelan, Ana Carolina; Machado, Eletilzia Severino; Borges, Michele do Rosário; Fancio, Célia Ribeiro; Lemes, Geni Aparecida de Oliveira (Seven Editora, 2026)
This chapter presents an expanded and in-depth version of the article entitled “Philosophy of praxis, gender and race: critical connections in the struggle of Black women”, published in the journal Contribuciones a las Ciencias Sociales, v. 19, n. 2, 2026. The aim of this text is to discuss how the philosophy of praxis, articulated with the contributions of Black feminism and intersectionality theory, enables the understanding of the multiple forms of oppression that shape the historical experience of Black women.The theoretical-methodological approach is based on a bibliographic review and theoretical analysis of authors from the Marxist tradition and contemporary critical thought, such as Karl Marx, Georg Lukács, Antonio Gramsci, and Paulo Freire, in dialogue with Black women thinkers such as Angela Davis, bell hooks, Lélia Gonzalez, and Sueli Carneiro.The analysis shows that the pedagogical and political practices developed by Black women constitute concrete forms of transformative praxis, articulating action, critical reflection, and everyday resistance against structures of domination. It concludes that the articulation between the philosophy of praxis and Black feminism contributes to building a critical and emancipatory perspective in the field of education and social sciences, reinforcing the need to recognize Black women as knowledge producers and central agents in the struggle for social justice.